Optical and Electrochemical Properties of a Photosensitive Pyromellitic Diimide Derivative of Cymantrene - Elena S. Kelbysheva; Mariam G. Ezernitskaya; Rinat R. Aysin; Tatyana V. Strelkova; Alexey N. Rodionov; Lyudmila N. Telegina (Molecules, 2023)
Photochemical properties of symmetrical pyromellitic diimide containing two cymantrenyl fragments at two nitrogen atoms were studied with IR, NMR, UV-vis, ESI-MS, and cyclic voltammetry. It was found that new unstable chelates are formed during photolysis. At the same time, the CO ligand dissociates from two Mn(CO)3 fragments during photoexcitation, which dramatically changes the electronic and redox properties of the molecule compared to the cymantrene derivative containing one imide fragment. Photolysis leads to a color change from light yellow to green. DFT calculations confirmed the possibility of the formation of complexes due to the loss of one or two CO ligands from manganese atoms. The results obtained with variation of photolysis conditions demonstrated the hemilabile character of the Mn-O=C(imide) bond. On addition of external ligands, the color and electrochemical properties changed, which is promising for the use of this complex as a sensor for small molecules.